Synthesis of 1-O-acyl- and 1-oxo-kamebanin analogues and their cytotoxic activity. (15th February 2023) - Aoyagi, Yutaka; Tomita, Kaori; Kobayashi, Asumi; Nakamura, Akari; Fujii, Yuki; Yagi, Momoka; Ichimaru, Yoshimi; Ozawa, Kei; Park, Hyun-Sun; Fukaya, Haruhiko; Yano, Reiko; Hasuda, Tomoyo; et al.
Graphical abstract: Abstract: A series of 1- O -acyl- and 1-oxo-kamebanin analogues were prepared from kamebanin, isolated from Rabdosia excisa and their cytotoxicity was assayed on HL60 promyelocytic leukemia cells and HCT116 human colon cancer cells. The structure–activity relationship study showed that the presence of 1- O -acyl groups of a C3 –C5 carbon chain increased the cytotoxic activity.